2017
DOI: 10.1103/physrevb.96.134407
|View full text |Cite
|
Sign up to set email alerts
|

First-principles and model simulation of all-optical spin reversal

Abstract: All-optical spin switching is a potential trailblazer for information storage and communication at an unprecedented fast rate and free of magnetic fields. However, the current wisdom is largely based on semiempirical models of effective magnetic fields and heat pulses, so it is difficult to provide high-speed design protocols for actual devices. Here, we carry out a massively parallel first-principles and model calculation for thirteen spin systems and magnetic layers, free of any effective field, to establish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…If we compare σ + and σ − , we find their final spins lie opposite to each other. This strong helicity dependence is consistent with our prior model study [45]. It is possible that our model does not include the itinerancy of the electrons sufficiently, so the helicity dependence is stronger from our model.…”
Section: A Dependence Of Demagnetization On System and Laser Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…If we compare σ + and σ − , we find their final spins lie opposite to each other. This strong helicity dependence is consistent with our prior model study [45]. It is possible that our model does not include the itinerancy of the electrons sufficiently, so the helicity dependence is stronger from our model.…”
Section: A Dependence Of Demagnetization On System and Laser Parameterssupporting
confidence: 89%
“…Once we initialize the spin along the −z axis, σ + and σ − are no longer equivalent because the spin determines the quantization axis. Figure 2 [45]. Once the spin points down, its effect is small.…”
Section: A Dependence Of Demagnetization On System and Laser Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…We recently showed that when one has a ferrimagnet [14], care must be taken because two different helicities act upon two respective sets of spins, leading to apparent HID switching.…”
Section: Introductionmentioning
confidence: 99%
“…Because optical selection rules depend on the spatial orientation of spins in a domain [14][15][16], even subject to the same laser beam, spins inside the domain wall behave differently.…”
Section: Introductionmentioning
confidence: 99%